The Impact of Body Weight on Ovarian Cancer Outcomes. Issue 9 (1st November 2011) - Backes, Floor J.; Nagel, Christa I.; Bussewitz, Elizabeth; Donner, Jessica; Hade, Erinn; Salani, Ritu
Abstract : Background: Obesity is a known risk factor and poor prognostic factor for many comorbidities including cancer. However, the influence of body mass index (BMI) on ovarian cancer outcomes is inconclusive. Therefore, the objective of this study was to evaluate the impact of BMI and weight changes on survival in patients with advanced ovarian cancer after primary treatment. Methods: All patients with a diagnosis of advanced epithelial ovarian cancer from January 2000 to December 2007 undergoing primary cytoreductive surgery and adjuvant chemotherapy were identified. Patients were divided into 3 categories: underweight/normal weight (BMI, <25 kg/m 2 ), overweight (BMI, 25–30 kg/m 2 ), and obese (BMI, >30 kg/m 2 ). Adjusted hazard ratios for progression-free survival (PFS) and overall survival (OS) were calculated via Cox proportional hazards models. Results: One hundred ninety-eight patients met the inclusion criteria. For all patients, the mean BMI was 26 kg/m 2 (range, 16.4–49.1 kg/m 2 ), with 43% of patients being classified as normal weight, 29% overweight, and 28% as obese. Median 5-year OS was 48.2 months (95% confidence interval, 16.4–49.1 months), and no differences in OS were noted between BMI groups. Unadjusted median PFS for patients with normal weight was 13.7 months, compared with 15.5 and 17.9 months for the overweight and obese groups. Adjusted analysis of BMI over time indicates a trend of increased risk for patients who gain weight in the 6 months after primary therapy on disease progression (hazard ratio, 1.68; 95% confidence interval, 0.87–3.26). Conclusions: After adjustment for confounders, such as stage, grade, histology, age, and debulking status, data suggest a trend toward a shorter PFS in patients with a normal BMI. However, OS was not significantly related to BMI, and weight change in the 6 months after completion of treatment had no effect on PFS or OS. Further research should be directed at elucidating relationships between weight and cancer biology.